" Use elimination to solve: 6x - y/4 = -9 and 3x + 2y = -30 "

Elimination here means eliminating/removing one of the variables. So if your problem is the y/4, then eliminate the y's. The other y-term is 2y, so you either

>>>make this 2y into y/4 by dividing 2y by 8, or,

>>>make the y/4 into 2y by multiplying the y/4 by 8. It is better this way so that you can avoid too many fractions.

6x -y/4 = -9

Multiply both sides by 8,

48x -2y = -72 -------------(i),

Add that to the other equation, to eliminate the y's,

3x +2y = -30

--------------

51x +0 = -102

x = -102 / 51

x = -2 -----------***

Substitute that into the other equation,

3(-2) +2y = -30

-6 +2y = -30

2y = -30 +6

2y = -24

y = -24/2

y = -12 ------------***

Check those in the 1st equation,

6x -y/4 = -9

6(-2) -(-12)/4 =? -9

-12 +3 =? -9

-9 =? -9

Yes, so, Ok.